Cancer chemotherapy-induced nausea and vomiting: role of mediators, development of drugs and treatment methods - Mahesh, R.; Perumal, R.V.; Vijayapandi, P. (2005)
The development of serotonin 5-HT3 receptor antagonists dramatically improved the treatment of chemotherapy-induced nausea and vomiting. Ondansetron, a serotonin 5-HT3 receptor antagonist in combination with dexamethasone is widely used to treat chemotherapy-induced nausea and vomiting. This treatment regimen is effective against acute nausea and vomiting, but fails to control delayed nausea and vomiting. Metoclopramide along with other antiemetics are used to treat delayed nausea and vomiting. The high doses of metoclopramide needed may produce extra pyramidal side effects. The recent developments of 5-HT3 and dopamine D-2 dual receptor antagonists have been found to exhibit a broad spectrum of activity against peripherally and centrally acting stimuli, but are not much effective against delayed emesis associated with chemotherapy. In various animal models, neurokinin NK1 receptor antagonists showed promising results against acute and delayed emesis, but the clinical trials revealed that triple therapy (NK1 receptor antagonist, 5-HT3 receptor antagonist and dexamethasone) is superior than standard therapy (5-HT3 receptor antagonist & dexamethasone) or NK1 receptor antagonist alone, in controlling acute as well as delayed nausea and vomiting. Ginger, which is used traditionally for controlling emesis induced by various stimuli, also showed good activity against chemotherapy-induced nausea and vomiting in animal models. Non-pharmacological methods such as acupressure and acustimulation are good adjunct methods in treating nausea and vomiting. Since many mediators are involved in emesis induced by chemotherapy, cocktail treatment is proven to be more efficacious than a single drug, but increases treatment costs. So there is a need of further research in this field to get economically useful methods for the treatment of acute and delayed chemotherapy-induced nausea and vomiting.